Dissolving microneedle-based intradermal delivery of interferon-α-2b. (2nd June 2016) - Chen, Jianmin; Qiu, Yuqin; Zhang, Suohui; Gao, Yunhua
Abstract: The dermal and transdermal delivery of protein pharmaceuticals faces enormous challenges, and at the same time, has very significant potential for the non-invasive treatment of both localized and systemic diseases. To demonstrate the pharmaceutical usefulness of dissolving microneedles (MNs) containing interferon-α-2b (IFN), IFN MNs were prepared using a new method. IFN were encapsulated in MNs with dose from 4.94 ± 0.64 to 23.79 ± 2.48 μg, and in vitro release test showed the efficiency reached 49.2%. After percutaneous administration of IFN MNs to rats, serum IFN levels were measured for 12 h. The peak serum IFN level, maximum drug concentration ( C max ), and the time to reach maximum concentration ( T max ), were 11.58 ± ng/ml and 40 min, respectively, for high-dose MNs group. The area under the curve (AUC) of MNs group was 28.85 ng·h/ml, while intramuscular injection (IM) group with equal dose was 31.17 ng·h/ml. Immunogenicity analysis showed the anti-IFN antibody got back to normal level at ninth week, and there was no difference between male and female rats. IFN MNs showed good stability for 2 months and no damage to the administered rats' skin. The results demonstrated the IFN MNs have a great potential to provide an alternative to IM.